2015
DOI: 10.1371/journal.pone.0121639
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Transmission from Healthcare Workers to Patients and Co-workers: A Systematic Literature Review and Meta-Analysis

Abstract: Healthcare workers (HCWs) are at risk of becoming infected with tuberculosis (TB), and potentially of being infectious themselves when they are ill. To assess the magnitude of healthcare-associated TB (HCA-TB) transmission from HCWs to patients and colleagues, we searched three electronic databases up to February 2014 to select primary studies on HCA-TB incidents in which a HCW was the index case and possibly exposed patients and co-workers were screened.We identified 34 studies out of 2,714 citations. In 29 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…A recent systematic review and meta-analysis on TB transmission from health workers to patients and other colleagues reveals that health workers with TB have lower TB transmission to their contacts than TB transmission by non-health worker index cases in households, schools and congregate and community settings. 16 However, all studies were performed in high-income and low TB burden countries, namely, the United States, the United Kingdom and France. The risk of TB transmission from health workers to contacts in this study may not be comparable to those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis on TB transmission from health workers to patients and other colleagues reveals that health workers with TB have lower TB transmission to their contacts than TB transmission by non-health worker index cases in households, schools and congregate and community settings. 16 However, all studies were performed in high-income and low TB burden countries, namely, the United States, the United Kingdom and France. The risk of TB transmission from health workers to contacts in this study may not be comparable to those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this group has lower transmission rates to contacts than other groups of infected individuals as a result of frequent health checks. 23 After close scrutiny of the screening data of 32 practitioners, Prof Nienhaus recommended an annual screen of HCW at high-risk due to contact with highly-infectious patients. However, screening guidelines issued by the public health systems of different countries suggest a varied combination of X-ray, tuberculin skin test (TST) and interferon-g release assays (IGRA) with no consensus on the best strategy.…”
Section: Tuberculosis: the Disease The Pathogen And The Hostmentioning
confidence: 99%
“…Tuberculosis (TB) spread within a healthcare facility is a major public health problem worldwide [ 1 ]. The early identification of cases after TB exposure plays a pivotal role in preventing further transmission of Mycobacterium tuberculosis [ 2 , 3 ]. Healthcare facilities, including facilities caring for subjects with mental illness and facilities with limited personal space, such as prisons and military camps, are characterized by an enclosed environment which leads to the inevitable close and long duration of contact between participants.…”
Section: Introductionmentioning
confidence: 99%